Catalyst, preparation method and application of catalyst in isomerization of olefinic unsaturated alcohol

By designing the unimodal distribution characteristics of palladium active components in the catalyst, the existing catalysts have solved the problems of many by-products, high separation costs and short catalyst life in the isomerization reaction of ethylenically unsaturated alcohols, and high efficiency and economical catalyst performance are achieved.

CN119819293APending Publication Date: 2025-04-15WANHUA CHEM GRP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510005874.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing catalysts have problems such as many by-products, high separation costs and short catalyst life in the isomerization reaction of ethylenically unsaturated alcohols, which are difficult to meet the economic and efficiency requirements of industrial applications.

Method used

A supported palladium-based catalyst was developed, with its palladium active components being single-peakedly distributed in the EDS line scanning spectrum. The peak tip is located 15-200μm inward in the support surface, and the peak width is not greater than 300μm. The peak intensity is controlled within a specific range to improve the activity, selectivity and lifetime of the catalyst.

Benefits of technology

The catalyst is achieved with high conversion, high selectivity and long life, and can be continuously produced in fixed bed reactors, with large processing volume and simple operation, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819293A_ABST
    Figure CN119819293A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst, a preparation method and application of the catalyst in isomerization of olefinic unsaturated alcohol. The catalyst comprises a carrier and a loaded active component, the carrier comprises aluminum oxide; the active component comprises palladium; the catalyst at least meets one of the following conditions in an EDS line scanning spectrogram: active components of the catalyst are in unimodal distribution from the surface of the carrier to the interior of the carrier on the outer surface layer of the carrier, and the peak tip of the unimodal distribution is positioned at a position 15-200 microns from the surface of the carrier to the interior of the carrier; the peak width of the single-peak distribution is not greater than 300 microns; the peak intensity from the surface of the carrier to the interior of the carrier by 15 microns is not more than 25%; and the peak intensity from the surface of the carrier to the center of the carrier from a position 200 mu m away from the interior of the carrier is not more than 10%. The catalyst can be applied to an olefinic unsaturated alcohol isomerization reaction, and is long in service life and high in activity and selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and particularly relates to a catalyst with unevenly distributed active components and a preparation method thereof, as well as application of the catalyst in isomerization of olefinic unsaturated alcohols. Background Art

[0002] 3-methyl-2-butene-1-ol, also known as isopentenol, is an important organic intermediate and can be used to produce various fine chemicals such as citral and spices. Compared with the existing production method using isoprene as raw material, the preparation method of isopentenol using isobutylene as raw material has low production cost and is basically pollution-free, and is an environmentally friendly and market-competitive production process route. The method firstly obtains 3-methyl-3-butene-1-ol (also known as isopentenol) by condensation reaction of isobutylene and formaldehyde, and then obtains isopentenol by isomerization reaction, and isomerization reaction is the key step to obtain isopentenol.

[0003] US4310709 reported a catalyst with carbon as carrier and active components of Pd and Se. Pd was modified by Se and Te and reacted in a reactor for 2 hours. The reaction yield reached 62% and the selectivity was 88.6%. This method has a large amount of over-hydrogenation by-products, which increases the separation cost, and the catalyst life is short, which increases the product production cost.

[0004] CN101544538 reports a catalyst with an alumina carrier and palladium as the active component. The catalyst particle size is 80-200 mesh and is suitable for a kettle reactor. The isopentenol yield can reach 67.7% and the isopentenol selectivity is 96.5%. However, this method still has a large amount of by-products, the separation cost is high, and the kettle batch reactor has a small processing capacity, which is not economical for industrial application.

[0005] Patent CN116272978 reports a composite metal aluminum catalyst and its preparation method and application. The catalyst adopts a one-pot method to prepare an alumina-loaded precious metal catalyst, uses aluminum isopropoxide, a template, a precious metal component, and a rare earth component to form a sol, and uses an oil-ammonia water system to form a spherical gel. The catalyst is obtained after washing, drying, calcining and reducing steps. The raw material cost of the catalyst is high and the preparation steps are complicated, which greatly increases the production cost of the catalyst.

[0006] Patent CN101965325 reports a method for isomerizing olefinic unsaturated alcohols, using a palladium-carbon catalyst and introducing a certain amount of oxygen gas to isomerize 3-methyl-3-butenol to form isopentenol. However, new impurities such as isopentenal are produced in the product. This method produces a large number of by-products for preparing isopentenol, has a high separation cost, and does not have an economic advantage.

[0007] Therefore, it is necessary to develop a new catalyst in the field, which can be better applied to the production of isomerization of olefinic unsaturated alcohols while ensuring the performance of the catalyst. Summary of the invention

[0008] In view of the above problems existing in the prior art, the present invention provides a catalyst and a preparation method thereof, wherein the catalyst is a supported palladium-based catalyst, and its palladium active component has the characteristic of being unimodal distributed from the outside to the inside. The catalyst of the present invention has low production cost, high catalytic activity, high selectivity, long service life, can adopt a fixed bed reactor, has a large processing capacity, and is simple to operate.

[0009] The present invention also provides a method for preparing isopentenol (3-methyl-2-butene-1-ol). The isopentenol is prepared by using the above catalyst in the isomerization reaction of isopentenol (3-methyl-3-butene-1-ol), and higher selectivity and yield can be achieved.

[0010] To achieve its purpose, the present invention adopts the following technical solutions:

[0011] In one aspect of the present invention, a catalyst is provided, the catalyst comprising a carrier and a supported active component;

[0012] The support comprises alumina; the active component comprises palladium;

[0013] The catalyst satisfies at least one of the following conditions in the EDS line scan spectrum:

[0014] The active components of the catalyst are distributed on the outer surface of the carrier in a single peak distribution from the carrier surface to the inside of the carrier, and the peak of the single peak distribution is located at 15-200 μm from the carrier surface to the inside of the carrier;

[0015] The peak width of the unimodal distribution is not greater than 300 μm, preferably not greater than 250 μm; the peak intensity at 15 μm from the surface of the carrier to the inside of the carrier is not greater than 25%, preferably not greater than 20%;

[0016] The peak intensity from the surface of the carrier to the center of the carrier at 200 μm inside the carrier is not more than 10%, preferably not more than 8%.

[0017] Specifically, the catalyst may at least satisfy the following conditions in the EDS line scan spectrum:

[0018] The peak tip of the unimodal distribution is located at 15 μm, 30 μm, 45 μm, 60 μm, 75 μm, 90 μm, 100 μm, 115 μm, 130 μm, 145 μm, 160 μm, 175 μm, 190 μm, 200 μm, etc. from the surface of the carrier to the inside of the carrier;

[0019] The peak width of the unimodal distribution is, for example, 300 μm, 290 μm, 280 μm, 260 μm, 240 μm, 220 μm, 200 μm, 180 μm, 160 μm, 130 μm, 100 μm, 80 μm, 50 μm, etc., and preferably the peak width is not greater than 250 μm;

[0020] The peak intensity at 15 μm from the carrier surface to the inside of the carrier is, for example, 25%, 22%, 20%, 18%, 15%, 13%, 10%, 8%, 5%, 3%, 1%, etc., preferably not more than 20%;

[0021] The peak intensity from the carrier surface to 200 μm inside the carrier to the center of the carrier is, for example, 10%, 8%, 5%, 3%, 1%, etc., and is preferably not more than 8%.

[0022] In a specific embodiment of the present invention, based on the total mass of the catalyst, the content of palladium is 0.3-10wt%, such as 0.3wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, etc., preferably 0.5-5wt%;

[0023] In a specific embodiment of the present invention, the particle size of the carrier is 1-10 mm, such as 1 mm, 3 mm, 5 mm, 8 mm, 10 mm, etc., preferably 2-8 mm;

[0024] The specific surface area of ​​the carrier is 50-300m 2 / g; pore volume is 0.4-0.9cm 3 / g; average pore size is 10-30nm;

[0025] The alumina contained in the carrier has a crystal form including one or more of γ-alumina, α-alumina, θ-alumina, and δ-alumina, preferably one or more of γ-alumina, θ-alumina, and δ-alumina.

[0026] In a specific embodiment of the present invention, the alumina contained in the carrier may be unmodified alumina or modified alumina;

[0027] In a specific example, the alumina is modified alumina, preferably alumina modified by alkali metal and / or alkaline earth metal; preferably, the alkali metal and alkaline earth metal are one or a combination of two or more of sodium, potassium, calcium and magnesium;

[0028] Preferably, the alkali metal and / or alkaline earth metal content is 0-5% of the mass of the modified alumina, such as 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, etc., preferably 0.1-4%.

[0029] The method of modifying alumina to obtain modified alumina is a prior art, and the present invention has no special requirements. The technicians can refer to the prior art and select any feasible method to prepare it according to experience. For example, the following method can be used for modification, and the steps include:

[0030] Alumina is uniformly mixed with optional alkali metal and alkaline earth metal compounds, and the mixture is dried and / or calcined to obtain the modified alumina.

[0031] Wherein, the alkali metal or alkaline earth metal compound is selected from at least one of alkali metal or alkaline earth metal hydroxides, carbonates, bicarbonates, metaaluminates, metasilicates, C1-C6 fatty acid salts, nitrates, chlorides, and oxides, preferably at least one of alkali metal or alkaline earth metal hydroxides, carbonates, bicarbonates, and C1-C6 fatty acid salts, more preferably one or a combination of two or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, magnesium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, sodium acetate, and potassium acetate;

[0032] The mass of the alkali metal and alkaline earth metal compound is 0.1-10% of the mass of aluminum oxide, such as 0.1%, 0.5%, 1%, 3%, 5%, 8%, 10%, etc., preferably 0.5-8%.

[0033] The mixing method may be one or a combination of two or more of conventional impregnation, precipitation, coating, physical mixing, etc., preferably at least one of the impregnation and coating methods;

[0034] In specific operations, an aqueous solution of an alkali metal or alkaline earth metal compound can be prepared as required. There is no specific requirement for the concentration, and it can usually be an aqueous solution of 0.5-5 wt%.

[0035] Wherein, the drying process temperature is 60-200°C, preferably 100-150°C, and the time is 1-10h;

[0036] The calcination process is carried out at a temperature of 200-800°C, preferably 250-500°C, and for a time of 1-10 hours.

[0037] In a specific embodiment of the present invention, the palladium contained in the active component can be a single substance of palladium metal, or a combination of palladium and other metals.

[0038] In a specific example, the palladium contained in the active component is a combination of palladium and other metals, and the other metals may be one or more of platinum, ruthenium, rhodium, etc.;

[0039] Preferably, based on the total mass of the catalyst, the content of the other metal is 0-3wt%, such as 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, etc., preferably 0.1-2wt%;

[0040] Preferably, the combination of palladium and other metals is a combination of palladium and platinum metal.

[0041] The inventor of the present application creatively discovered that by limiting the catalyst to the above-mentioned supported palladium-based catalyst and making the active component of the catalyst at least meet the above-mentioned conditions in the EDS line scanning spectrum, not only the preparation method of the catalyst itself is simple, but also has the advantages of low production cost, high activity, high selectivity, long life, and can use a fixed bed reactor, large processing capacity, etc. When it is used to catalyze the isomerization of isopentenol to prepare isopentenol, a higher selectivity and yield can be achieved. After analysis, the inventor found that it is mainly because: the active component is unimodal distribution, and the peak of the unimodal distribution is located at 15μm-200μm from the outermost layer to the catalyst inward, and the concentration of the active component at this place is high. After the raw material contacts with the high concentration of active components under the reaction conditions, the double bond can be rapidly isomerized, and the catalytic activity is significantly improved; at the same time, the active component at this place is close to the outer layer of the catalyst, and the reaction product can be rapidly desorbed, which inhibits the occurrence of excessive hydrogenation side reactions and improves product selectivity; the active component at this place is not easy to lose, which prolongs the service life of the catalyst.

[0042] In another aspect of the present invention, a method for preparing the catalyst as described above is provided, wherein the catalyst is a supported solid catalyst and can be prepared by conventional methods in the field, and the present invention does not make specific requirements. For example, the active component can be contacted with the carrier by impregnation, precipitation, coating, physical blending, etc., and then reduced to obtain the catalyst.

[0043] Specifically, a method for preparing one of the catalysts is described by way of example, the steps comprising:

[0044] The solution containing the active component compound is contacted with the support, and the solution is washed, dried and / or calcined to obtain a catalyst precursor;

[0045] The catalyst precursor is subjected to reduction treatment to obtain the catalyst.

[0046] In a specific embodiment of the present invention, the solution containing the active component compound has a temperature of 20-100°C, preferably 25-80°C;

[0047] The solution containing the active component compound is a solution containing a palladium compound and optionally other metal compounds, wherein the other metal is one or more of platinum, ruthenium, rhodium, etc., preferably platinum;

[0048] Preferably, the solution containing the active component compound is an aqueous solution containing the active component compound, wherein the concentration of palladium element is 1-20 g / L, preferably 2-10 g / L, and the concentration of other metal elements is 0-8 g / L, preferably 0.1-5 g / L;

[0049] Preferably, the palladium compound includes at least one or more of palladium chloride, sodium chloropalladate, palladium nitrate, palladium acetate, ammonium tetrachloropalladate, and dichlorotetraamminepalladium, preferably at least one or more of palladium chloride and sodium chloropalladate;

[0050] The other metal compound is a soluble compound of other metals, preferably a platinum compound;

[0051] The platinum compound is selected from at least one or more of chloroplatinic acid, sodium chloroplatinate, and platinum nitrate, preferably at least one or more of chloroplatinic acid and sodium chloroplatinate.

[0052] In a specific embodiment of the present invention, there is no specific requirement for the contact method, and at least one of conventional impregnation method, precipitation method, coating method, physical mixing method, etc. can be adopted, preferably at least one of impregnation method and coating method; the contact time is 1-48h, preferably 2-24h.

[0053] In a specific embodiment of the present invention, when the solution containing the active component compound contacts the carrier, the mass ratio of the solution containing the active component compound to the carrier is 0.3-5, preferably 0.5-4.5.

[0054] In a specific embodiment of the present invention, the drying process is carried out at a temperature of 60-200°C, preferably 100-150°C, for a time of 1-10h;

[0055] The calcination process is carried out at a temperature of 200-800°C, preferably 250-500°C, and for a time of 1-10 hours.

[0056] In a specific embodiment of the present invention, the catalyst precursor is subjected to reduction treatment by at least one of gas phase reduction and liquid phase reduction;

[0057] Wherein, the gas phase reduction, the reducing gas is selected from at least one of hydrogen, ethylene and propylene, preferably hydrogen; the gas phase reduction temperature is 100-600°C, preferably 150-500°C; the gas phase reduction time is 1-10h, preferably 2-8h, and the pressure is 0-4MPa;

[0058] The liquid phase reduction is carried out in a solution of a reducing agent, preferably an aqueous solution of the reducing agent, and there is no special requirement for its concentration, for example, the concentration can be 0.1-5wt%; the reducing agent is selected from at least one of sodium formate, hydrazine hydrate, sodium borohydride, formaldehyde, and glucose, preferably sodium formate, hydrazine hydrate, and sodium borohydride; the amount of the reducing agent is 1-10 times, preferably 1.5-8 times, of the theoretical amount required to reduce the active component compound or the active component oxide obtained by calcination conversion to the corresponding element; the liquid phase reduction temperature is 15-100°C, and the time is 0.5-24h.

[0059] In another aspect of the present invention, there is provided use of the above catalyst or the catalyst prepared according to the above method in isomerization of olefinically unsaturated alcohols.

[0060] The olefinically unsaturated alcohols include 3-methyl-3-butene-1-ol (isoprenol), 3-butene-1-ol, 3-pentene-1-ol, 3-hexene-1-ol, 3-methylpent-3-ene-1-ol and the like.

[0061] In a specific embodiment of the present invention, the use of the olefinic unsaturated alcohol isomerization includes the use of the above-mentioned catalyst, or the catalyst obtained by the above-mentioned preparation method, to isomerize 3-methyl-3-butene-1-ol (isoprenol) into 3-methyl-2-butene-1-ol (isoprenol).

[0062] Specifically, the method for isomerizing 3-methyl-3-butene-1-ol to 3-methyl-2-butene-1-ol as described above can be adopted by referring to the existing process and carrying out the isomerization reaction through a conventional reactor in the art. For example, the reactor used can be a fixed bed reactor, and it can be a continuous reaction or a batch reaction.

[0063] In a specific example, a method for isomerizing 3-methyl-3-butene-1-ol to 3-methyl-2-butene-1-ol comprises the following steps:

[0064] The catalyst is loaded into a fixed bed reactor for reaction, and a hydrogen-containing carrier gas and 3-methyl-3-butene-1-ol are introduced into the reactor for isomerization reaction to obtain 3-methyl-2-butene-1-ol;

[0065] Wherein, the space velocity of the hydrogen-containing carrier gas is 20-800h -1 , preferably 50-500h -1 ;

[0066] Preferably, the hydrogen content in the hydrogen-containing carrier gas is 0.5-10% (v / v), preferably 0.5-5% (v / v), and the rest is nitrogen;

[0067] The volume space velocity of the 3-methyl-3-butene-1-ol is 0.3-30h -1 , preferably 0.5-10h -1 ;

[0068] The isomerization reaction has a reaction temperature of 80-300°C, preferably 100-180°C, and a reaction pressure of 0.1-3MPa, preferably 0.1-2MPa.

[0069] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in the following aspects:

[0070] 1) The present invention provides a novel catalyst in which the active components are unimodally distributed from the outside to the inside on an alumina carrier, and the catalyst has the advantages of high conversion rate, high selectivity and long life;

[0071] 2) The catalyst preparation process of the present invention is simpler, the raw material cost is lower, and the catalyst production cost is saved.

[0072] 3) Compared with the existing catalyst technology, the catalyst provided by the present invention can be applied to the continuous production of fixed bed reactor, has a large processing capacity, is simple to operate, and is better applied to the industrial production of isomerization of olefinic unsaturated alcohols. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] Figure 1 This is the EDS line scanning spectrum of the catalyst prepared in Example 1. DETAILED DESCRIPTION

[0074] The following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the rights claimed by the present invention.

[0075] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered as specifically disclosed in this article.

[0076] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially.

[0077] In each embodiment and comparative example of the present invention, the sources of the main raw materials used are as follows:

[0078] Alumina pellets, Wufeng Aluminum and Magnesium Technology Co., Ltd.;

[0079] 3-Methyl-3-butene-1-ol, 99.5%, Aladdin Reagent Co., Ltd.;

[0080] Unless otherwise specified, other raw materials are conventional commercially available raw materials.

[0081] The main test methods used in the embodiments of the present invention and the comparative examples are as follows:

[0082] 1. Product analysis method: The content of each component in the reaction product was analyzed by gas chromatography using Agilent GC 8890A chromatograph and chromatographic column DB-5 (30m×320μm×0.25μm). In the examples, the selectivity and yield were calculated using the following formula:

[0083]

[0084] 2. Determination method of specific surface area and pore structure information

[0085] The pore structure was determined by N2 physical adsorption;

[0086] The specific surface area was calculated using the BET method;

[0087] The pore volume was obtained by BJH desorption method, and the testing instrument model was Micromeritics ASAP 2460.

[0088] 3. Determination of distribution of active components of catalyst

[0089] EDS line scan spectrum: The sample was measured by electron probe radial line analysis (line analysis) scanning using a scanning electron microscope (SEM) equipped with an energy dispersive spectrometer (EDS). The catalyst sample was placed in an embedding container, epoxy resin was dripped into it, and the epoxy resin was heated and cured after it fully penetrated into the catalyst. The sample was polished to the position of the largest cross-section of the catalyst particles, and the polished sample section was glued upward on the sample stage. A layer of carbon was coated on the surface of the sample. The SEM-EDS instrument was used to scan from the outermost layer of the catalyst cross-section to the center layer of the catalyst.

[0090] Test conditions:

[0091] Accelerating voltage: 15kv;

[0092] Working distance: 10mm;

[0093] Scanning method: hierarchical scanning.

[0094] Example 1

[0095] 1) Preparation of catalyst

[0096] Take 1kg of alumina balls (average particle size 2mm, specific surface area 211m2 / g, pore volume of 0.85mL / g, average pore size of 12.5nm, γ-alumina), prepare 800mL of an aqueous solution containing 36.2g of sodium bicarbonate, mix it thoroughly with the alumina balls, and then put it into an oven at 150°C and dry it for 2h to obtain sodium-modified alumina, with a sodium content of 1.0% of the mass of the modified alumina.

[0097] Prepare 3.0L of an aqueous solution containing 41.6g of sodium chloropalladate (with a palladium concentration of 5.0g / L), add a sodium-modified alumina carrier (with a mass ratio of the aqueous solution to the carrier of 3.0), stir thoroughly at 30°C, let stand for 24h, then wash thoroughly with deionized water until no chloride ions are detected, put into an oven at 150°C and dry for 8h to obtain a catalyst precursor; then dissolve 18g of a 40wt% hydrazine hydrate solution in 2.5L of water (the amount of hydrazine hydrate used is twice the theoretical amount required to reduce sodium chloropalladate to a single palladium substance), put into the catalyst precursor, reduce at 25°C for 4h, wash thoroughly, and then put into an oven at 100°C to dry to obtain a finished catalyst product, in which the palladium content is 1.5wt%.

[0098] The distribution of active components of the catalyst is shown in Figure 1 (EDS line scanning spectrum), in which the active component is on the outer layer of the carrier, and is distributed in a single peak from the carrier surface to the inside of the carrier, with the peak tip located at 56.8μm from the carrier surface to the inside of the carrier, and the peak width of the single peak distribution is 144.9μm. The peak intensity of the catalyst from the carrier surface to the inside of the carrier at 15μm is 10.4%; the peak intensity of the catalyst from the carrier surface to the inside of the carrier at 200μm to the center of the carrier is 0.4%.

[0099] 2) Catalyst performance test

[0100] 300 ml of catalyst was filled into a fixed bed reactor, and hydrogen-containing carrier gas and 3-methyl-3-butene-1-ol were passed through the reactor from top to bottom. The flow rate of hydrogen-containing carrier gas was 75 L / h, the feed rate of 3-methyl-3-butene-1-ol was 1500 ml / h, and the space velocity of hydrogen-containing carrier gas was 250 h -1 , the volume space velocity of 3-methyl-3-butene-1-ol is 5h -1 The reaction temperature was 150°C, the reaction pressure was 0.1 MPa, the hydrogen content in the hydrogen-containing carrier gas was 4% (v / v), and the rest was nitrogen. After the product was discharged from the reactor outlet, it was condensed through a heat exchanger. The condensed sample was analyzed by gas chromatography to determine the composition of the reaction liquid. The reaction results are shown in Table 1.

[0101] Example 2

[0102] 1) Preparation of catalyst

[0103] Take 1kg of alumina balls (average particle size 5mm, specific surface area 120m 2 / g, pore volume of 0.75mL / g, average pore size of 20.0nm, δ, θ-alumina mixed crystal form), prepare 743mL of an aqueous solution containing 3.4g of sodium hydroxide, mix it thoroughly with the alumina balls, and then put it into an oven at 100°C and dry it for 1h to obtain sodium-modified alumina, and the sodium content is 0.1% of the mass of the modified alumina.

[0104] Prepare 2.0L of an aqueous solution containing 8.35g of palladium chloride (palladium element concentration of 2.5g / L) and 10.5g of chloroplatinic acid hexahydrate (platinum element concentration of 2.5g / L), add a sodium-modified alumina carrier (the mass ratio of the aqueous solution to the carrier is 2.0), stir thoroughly at 45°C, let stand for 8h, then wash thoroughly with deionized water until no chloride ions are detected, put into an oven at 100°C and dry for 6h to obtain a catalyst precursor; put the catalyst precursor into a reduction reactor, introduce hydrogen at a pressure of 0.1MPa, and reduce at 250°C for 4h to obtain a finished catalyst product, in which the palladium content is 0.5wt% and the platinum content is 0.5wt%.

[0105] The active components of the catalyst are distributed unimodally on the outer surface of the carrier from the surface of the carrier to the inside of the carrier, with the peak tip located 103.6 μm from the surface of the carrier to the inside of the carrier, the peak width of the unimodal distribution is 215.6 μm, and the peak intensity of the catalyst at 15 μm from the surface of the carrier to the inside of the carrier is 5.7%; the peak intensity of the catalyst from 200 μm from the surface of the carrier to the center of the carrier is 5.2%.

[0106] 2) Catalyst performance test

[0107] The catalyst evaluation conditions were the same as those in Example 1. After the product was discharged from the reactor outlet, it was condensed through a heat exchanger. The condensed sample was analyzed by gas chromatography to determine the composition of the reaction liquid. The reaction results are shown in Table 1.

[0108] Example 3

[0109] 1) Preparation of catalyst

[0110] Take 1kg of alumina balls (average particle size 4.5mm, specific surface area 101m 2 / g, pore volume of 0.79mL / g, average pore size of 21.3nm, θ-alumina), prepare 755mL of an aqueous solution containing 50.1g of potassium acetate, mix it thoroughly with the alumina balls, and then put it into a muffle furnace and calcine at 300℃ for 2h to obtain potassium-modified alumina, with a potassium content of 2.0% of the mass of the modified alumina.

[0111] Prepare 4L of an aqueous solution containing 144.2g of sodium chloropalladate (palladium element concentration of 13.0g / L), add a potassium-modified alumina carrier (the mass ratio of the aqueous solution to the carrier is 4.0), stir thoroughly at 25°C, let stand for 2h, then wash thoroughly with deionized water until no chloride ions are detected, put into an oven at 120°C and dry for 4h to obtain a catalyst precursor; put the catalyst precursor into a reduction reactor, introduce hydrogen at a pressure of 2MPa, and reduce at 400°C for 2h to obtain a finished catalyst product, in which the palladium content is 5wt%.

[0112] The active components of the catalyst are distributed unimodally on the outer surface of the carrier from the surface of the carrier to the inside of the carrier, with the peak tip located 200.3 μm from the surface of the carrier to the inside of the carrier, the peak width of the unimodal distribution is 280.1 μm, and the peak intensity of the catalyst at 15 μm from the surface of the carrier to the inside of the carrier is 2.7%; the peak intensity of the catalyst from 200 μm from the surface of the carrier to the center of the carrier is 8.0%.

[0113] 2) Catalyst performance test

[0114] The catalyst evaluation conditions were the same as those in Example 1. After the product was discharged from the reactor outlet, it was condensed through a heat exchanger. The condensed sample was analyzed by gas chromatography to determine the composition of the reaction liquid. The reaction results are shown in Table 1.

[0115] Example 4

[0116] 1) Preparation of catalyst

[0117] Take 1kg of alumina balls (average particle size 2.5mm, specific surface area 101m 2 / g, pore volume of 0.79mL / g, average pore size of 21.3nm, θ-alumina), an aqueous solution containing 23.2g of sodium carbonate is fully mixed with the alumina balls, and then placed in an oven at 120°C for 2h to obtain sodium-modified alumina, and the potassium content is 0.5% of the mass of the modified alumina.

[0118] Prepare 2.4L of an aqueous solution containing 28.0g of sodium chloropalladate (palladium element concentration of 4.2g / L), add a sodium-modified alumina carrier (the mass ratio of the aqueous solution to the carrier is 2.4), stir thoroughly at 80°C, let stand for 12h, then wash thoroughly with deionized water until no chloride ions are detected, put into a muffle furnace and calcine at 400°C for 4h to obtain a catalyst precursor; then dissolve 32.5g of sodium formate in 3.0L of water (the amount of sodium formate is 5 times the theoretical amount required to reduce sodium chloropalladate to a single palladium substance), put into the catalyst precursor, reduce at 80°C for 4h, wash thoroughly, and put into an oven at 120°C for drying to obtain a finished catalyst, in which the palladium content is 1.0wt%.

[0119] The active components of the catalyst are distributed unimodally on the outer surface of the carrier from the surface of the carrier to the inside of the carrier, with the peak tip located 27.2 μm from the surface of the carrier to the inside of the carrier, the peak width of the unimodal distribution is 153.8 μm, and the peak intensity of the catalyst at 15 μm from the surface of the carrier to the inside of the carrier is 18.6%; the peak intensity of the catalyst from 200 μm from the surface of the carrier to the center of the carrier is 0.9%.

[0120] 2) Catalyst performance test

[0121] The catalyst evaluation conditions were the same as those in Example 1. After the product was discharged from the reactor outlet, it was condensed through a heat exchanger. The condensed sample was analyzed by gas chromatography to determine the composition of the reaction liquid. The reaction results are shown in Table 1.

[0122] Comparative Example 1

[0123] Take 1kg of alumina balls (average particle size 2.5mm, specific surface area 101m 2 / g, pore volume of 0.79mL / g, average pore size of 21.3nm, θ-alumina), prepare 800mL of an aqueous solution containing 28g of sodium chloropalladate, mix the alumina balls and the sodium chloropalladate aqueous solution evenly, let stand for 24h, put into an oven at 150°C for drying to obtain a catalyst precursor; then dissolve 132.5g of sodium formate in 3.0L of water (the amount of sodium formate is 5 times the theoretical amount required to reduce sodium chloropalladate to palladium element), put into the catalyst precursor, reduce at 80°C for 4h, wash thoroughly, put into an oven at 120°C for drying to obtain a finished catalyst product, in which the palladium content is 1.0wt%.

[0124] The active components of the catalyst are evenly distributed.

[0125] The catalyst evaluation conditions were the same as those in Example 1. After the product was discharged from the reactor outlet, it was condensed through a heat exchanger. The condensed sample was analyzed by gas chromatography to determine the composition of the reaction liquid. The reaction results are shown in Table 1.

[0126] Table 1 Catalyst performance evaluation reaction results of Examples and Comparative Examples

[0127] Serial number Selectivity / % Yield / % Example 1 99.5 69.7 Example 2 99.8 68.2 Example 3 99.2 66.7 Example 4 99.6 70.5 Comparative Example 1 82.4 56.4

[0128] Catalyst life evaluation experiment

[0129] The catalyst prepared in Example 1 was subjected to a long-term life evaluation, and the reaction results at different operating times are shown in Table 2.

[0130] Table 2 Example 1 Catalyst long cycle life evaluation reaction results

[0131] Running time / h Selectivity / % Yield / % 4 99.5 69.7 24 99.8 70.1 48 99.8 70.7 100 99.6 70.2 500 99.7 70.0 1000 99.8 70.1 3000 99.6 69.9 5000 99.6 69.8 7000 99.5 69.6

[0132] It can be seen from the examples and comparative examples that the activity and selectivity of the catalyst in which the active component is unimodally distributed on the carrier are significantly higher than those of the catalyst in which the active component is uniform. At the same time, the catalyst of the present invention has a long service life, effectively improves the catalytic reaction activity, inhibits the occurrence of side reactions, improves the selectivity of the target product, and has the advantage of saving costs.

[0133] Although the present invention has been described in detail for the purpose of illustration in the foregoing text, it should be understood that these detailed descriptions are only for illustration and can be modified by those skilled in the art without departing from the spirit and scope of the present invention. The present invention is limited only by the claims.

Claims

1. A catalyst, characterized in that comprising a carrier and a loaded active component; The support comprises alumina; the active component comprises palladium; The catalyst satisfies at least one of the following conditions in the EDS line scan spectrum: The active components of the catalyst are distributed on the outer surface of the carrier in a single peak distribution from the carrier surface to the inside of the carrier, and the peak of the single peak distribution is located at 15-200 μm from the carrier surface to the inside of the carrier; The peak width of the unimodal distribution is not greater than 300 μm, preferably the peak width is not greater than 250 μm; The peak intensity at 15 μm from the carrier surface to the inside of the carrier is not more than 25%, preferably not more than 20%; The peak intensity from the surface of the carrier to the center of the carrier at 200 μm inside the carrier is not more than 10%, preferably not more than 8%.

2. The catalyst according to claim 1, characterized in that Based on the total mass of the catalyst, the palladium content is 0.3-10wt%, preferably 0.5-5wt%; and / or The particle size of the carrier is 1-10 mm, preferably 2-8 mm; and / or The specific surface area of ​​the carrier is 50-300m 2 / g; pore volume is 0.4-0.9cm 3 / g; average pore size of 10-30nm; and / or The alumina, its crystal form includes one or more of γ-alumina, α-alumina, θ-alumina, δ-alumina, preferably one or more of γ-alumina, θ-alumina, δ-alumina.

3. The catalyst according to claim 1, characterized in that The alumina is unmodified alumina or modified alumina; The modified alumina is preferably alumina modified by alkali metal and / or alkaline earth metal; preferably, the alkali metal and alkaline earth metal are one or a combination of two or more of sodium, potassium, calcium and magnesium; Preferably, the alkali metal and / or alkaline earth metal content is 0-5%, preferably 0.1-4%, of the mass of the modified alumina.

4. The catalyst according to claim 1, characterized in that The palladium is a single substance of palladium metal, or a combination of palladium and other metals; The combination of palladium and other metals, wherein the other metals are one or more of platinum, ruthenium, rhodium, etc.; Preferably, based on the total mass of the catalyst, the content of the other metal is 0-3wt%, preferably 0.1-2wt%; Preferably, the combination of palladium and other metals is a combination of palladium and platinum metal.

5. A method for preparing the catalyst according to any one of claims 1 to 4, characterized in that the steps include: The solution containing the active component compound is contacted with the support, and the solution is washed, dried and / or calcined to obtain a catalyst precursor; The catalyst precursor is subjected to reduction treatment to obtain the catalyst.

6. The preparation method according to claim 5, characterized in that: The solution containing the active ingredient compound has a temperature of 20-100°C, preferably 25-80°C; and / or The solution containing the active component compound is a solution containing a palladium compound and optionally other metal compounds, wherein the other metal is one or more of platinum, ruthenium, rhodium, etc., preferably platinum; Preferably, the solution containing the active component compound is an aqueous solution containing the active component compound, wherein the concentration of palladium element is 1-20 g / L, preferably 2-10 g / L, and the concentration of other metal elements is 0-8 g / L, preferably 0.1-5 g / L; Preferably, the palladium compound includes at least one or more of palladium chloride, sodium chloropalladate, palladium nitrate, palladium acetate, ammonium tetrachloropalladate, and dichlorotetraamminepalladium, preferably at least one or more of palladium chloride and sodium chloropalladate; Preferably, the other metal compound is a soluble compound of other metals, preferably a platinum compound; More preferably, the platinum compound is selected from at least one or more of chloroplatinic acid, sodium chloroplatinate, and platinum nitrate, preferably at least one or more of chloroplatinic acid and sodium chloroplatinate.

7. The preparation method according to claim 5, characterized in that: The contact method is selected from at least one of an impregnation method, a precipitation method, a coating method, and a physical mixing method, preferably at least one of an impregnation method and a coating method; the contact time is 1-48 hours, preferably 2-24 hours; and / or The mass ratio of the solution of the active component compound to the carrier is 0.3-5, preferably 0.5-4.5; and / or The drying process is carried out at a temperature of 60-200°C, preferably 100-150°C, for a time of 1-10 hours; and / or The calcination process is carried out at a temperature of 200-800°C, preferably 250-500°C, and for a time of 1-10 hours.

8. The preparation method according to claim 5, characterized in that: The catalyst precursor is subjected to reduction treatment by at least one of gas phase reduction and liquid phase reduction; Preferably, in the gas phase reduction, the reducing gas is at least one of hydrogen, ethylene and propylene, preferably hydrogen; the gas phase reduction temperature is 100-600°C, preferably 150-500°C; the gas phase reduction time is 1-10h, preferably 2-8h, and the pressure is 0-4MPa; Preferably, in the liquid phase reduction, the reducing agent is selected from at least one of sodium formate, hydrazine hydrate, sodium borohydride, formaldehyde and glucose, preferably at least one of sodium formate, hydrazine hydrate and sodium borohydride; the amount of the reducing agent is 1-10 times, preferably 1.5-8 times, of the theoretical amount required to reduce the active component compound or the active component oxide obtained by calcination conversion to the corresponding element; the liquid phase reduction temperature is 15-100°C, and the time is 0.5-24h.

9. Use of the catalyst according to any one of claims 1 to 4 or the catalyst prepared by the method according to any one of claims 5 to 8 in the isomerization of olefinically unsaturated alcohols; Preferably, the olefinically unsaturated alcohol comprises one of 3-methyl-3-butene-1-ol (isoprene alcohol), 3-butene-1-ol, 3-pentene-1-ol, 3-hexene-1-ol, and 3-methylpent-3-ene-1-ol.

10. A method for isomerizing 3-methyl-3-butene-1-ol to 3-methyl-2-butene-1-ol, characterized in that the steps include: The catalyst is loaded into a fixed bed reactor for reaction, and a hydrogen-containing carrier gas and 3-methyl-3-butene-1-ol are introduced into the reactor for isomerization reaction to obtain 3-methyl-2-butene-1-ol; The catalyst is the catalyst according to any one of claims 1 to 4 or the catalyst prepared by the method according to any one of claims 5 to 8; Preferably, the space velocity of the hydrogen-containing carrier gas is 20-800h -1 , preferably 50-500h -1 ; Preferably, the hydrogen content in the hydrogen-containing carrier gas is 0.5-10% (v / v), preferably 0.5-5% (v / v), and the rest is nitrogen; Preferably, the volume space velocity of the 3-methyl-3-butene-1-ol is 0.3-30h -1 , preferably 0.5-10h -1 ; Preferably, the isomerization reaction has a reaction temperature of 80-300°C, preferably 100-180°C, and a reaction pressure of 0.1-3MPa, preferably 0.1-2MPa.

Citation Information

Patent Citations

  • Manufacture of but-2-en-1-ol compounds by isomerizing the corresponding but-3-en-1-ol compounds

    US4310709A